Effect of Life Expectancy on Technological Development - Amandeep Singh; Kuldeep Kumar; Jasneet Kaur Wadhwa; Palakkandy, Arun (Technium Social Sciences Journal, 2021)
The manuscript looks into the improvement of Life Expectancy and the number of invention patents filed in USA over the last two centuries. The direct proportionality between Technological advancement and Life Expectancy proves that the two indices are corelated. However, the corelation when viewed with the lag present between Life Expectancy and Technological advancement indicates that the Technological advancement depends on the Life Expectancy and not visa versa. This notionally proves increased Life expectancy as the cause to Technological developments being made in USA.